PERANCANGAN ULANG SISTEM SUSPENSI SHOCKBREAKER PADA KENDARAAN BIMANTARA NENGGALA - Sukahar; Hafid, Achmad; Suparja (PPM Sdirjianbang Akademi Militer, 2025)
This study focuses on redesigning the shock absorber suspension system of the Bimantara Nenggala vehicle, which is used as a service vehicle at the Military Academy, to enhance durability on rough road surfaces. The modification was carried out by increasing the diameter of the steel spring wire from 14 mm to 16 mm. The results indicate that this change increased the solid length of the spring from 56 mm to 96 mm, the number of coils from 2.5 to 4.5, and the spring deflection from 39.38 mm to 41.48 mm. This redesign demonstrates that using a 16 mm wire diameter provides better performance compared to the 14 mm wire, with improved durability, deflection, and coil count for optimal suspension efficiency.